The development of success in Swedish biathlon - Carlson, R. (LASE Journal of Sport Science, 2010)
The purpose of this study was to contribute to an explanation why Swedes of both sexes achieved great international success simultaneously in a small national sport such as biathlon. The elite group consisted of the male and female national team. A control group matched in pairs was identified in variables age, sex and athletic performance. All investigated athletes were products of the Swedish sport academy system (RIG, upper secondary education). Data were collected via interviews with athletes, national coaches and managers. Compared to the controls, elite athletes were more often born early in a year, less injured and less sick during RIG years and experienced coaches more favourable in terms of acting and individualisation.